Rethinking organic wastes bioconversion: Evaluating the potential of the black soldier fly (Hermetia illucens (L.)) (Diptera: Stratiomyidae) (BSF). (November 2020) - Surendra, K.C.; Tomberlin, Jeffery K.; van Huis, Arnold; Cammack, Jonathan A.; Heckmann, Lars-Henrik L.; Khanal, Samir Kumar
Highlights: BSF-based biorefinery could valorize organic wastes into biobased products. BSF biomass could substitute a substantial amount protein and fat in animal diets. BSF biomass is rich in bioactive compounds and enhances the nutritive value as feed. Automation and process scale up are needed for exploitation of BSF technology. Abstract: Population growth and unprecedented economic growth and urbanization, especially in low- and middle-income countries, coupled with extreme weather patterns, the high-environmental footprint of agricultural practices, and disposal-oriented waste management practices, require significant changes in the ways we produce food, feed and fuel, and manage enormous amounts of organic wastes. Farming insects such as the black soldier fly (BSF) ( Hermetia illucens ) on diverse organic wastes provides an opportunity for producing nutrient-rich animal feed, fuel, organic fertilizer, and biobased products with concurrent valorization of wastes. Inclusion of BSF larvae/pupae in the diets of poultry, fish, and swine has shown promise as a potential substitute of conventional feed ingredients such as soybean meal and fish meal. Moreover, the bioactive compounds such as antimicrobial peptides, medium chain fatty acids, and chitin and its derivatives present in BSF larvae/pupae, could also add values to the animal diets. However, to realize the full potential of BSF-based biorefining, more research and development efforts are necessary for scaling up the production and processing of BSF biomass using more mechanized and automated systems. More studies are also needed to ensure the safety of the BSF biomass grown on various organic wastes for animal feed (also food) and legalizing the feed application of BSF biomass to wider categories of animals. This critical review presents the current status of the BSF technology, identifies the research gaps, highlights the challenges towards industrial scale production, and provides future perspectives.